Sociocultural factors influencing breastfeeding practices in two slums in Nairobi, Kenya. Issue 1 (December 2016) - Wanjohi, Milka; Griffiths, Paula; Wekesah, Frederick; Muriuki, Peter; Muhia, Nelson; Musoke, Rachel; Fouts, Hillary; Madise, Nyovani; Kimani-Murage, Elizabeth
Abstract Background Despite numerous interventions promoting optimal breastfeeding practices in Kenya, pockets of suboptimal breastfeeding practices are documented in Kenya's urban slums. This paper describes cultural and social beliefs and practices that influence breastfeeding in two urban slums in Nairobi, Kenya. Methods Qualitative data were collected in Korogocho and Viwandani slums through 10 focus group discussions and 19 in-depth interviews with pregnant, breastfeeding women and community health volunteers and 11 key-informant interviews with community leaders. Interviews were audiotaped, transcribed verbatim, coded in NVIVO and analyzed thematically. Results Social and cultural beliefs and practices that result to suboptimal breastfeeding practices were highlighted including; considering colostrum as 'dirty' or 'curdled milk', a curse 'bad omen' associated with breastfeeding while engaging in extra marital affairs, a fear of the 'evil eye' (malevolent glare which is believed to be a curse associated with witchcraft) when breastfeeding in public and breastfeeding being associated with sagging breasts. Positive social and cultural beliefs were also identified including the association of breast milk with intellectual development and good child health. The beliefs and practices were learnt mainly from spouses, close relatives and peers. Conclusion Interventions promoting behavior change with regards to breastfeeding should focus on dispelling the beliefs and practices that result to suboptimal breastfeeding practices and to build on the positive ones, while involving spouses and other family members as they are important sources of information on breastfeeding. Trial registration ISRCTN83692672 : December 2013 (retrospectively registered)